Pengetahuan dan Sikap Stigma Mahasiswa Kebidanan Stikes Kuningan Terhadap Orang Dengan HIV/AIDS (Odha) - Saprudin, Ade; Jatiningsih, Sri; Heriana, Cecep (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2015)
Stigma and discrimination against people living with HIV is still a problem in Indonesia and this not only by society but also it can be occurred by the student who studies in health and health care providers who have a comprehensive knowledge about HIV / AIDS. The purpose of this research is to determine the relationship of knowledge about HIV / AIDS with attitudes stigma towards people living with HIV in Midwifery students at Kuningan School of Health Sciences. Cross-sectional study design has been used with a sample of 130 students of midwifery by Proportional Random Sampling technique. Univariate and bivariate analysis methods has been used with the Chi-square statistical test. The results of the research show that, as much as 35% of students have a good knowledge and highest 72.3% of the students have a good stigma against people living with HIV. Results Bivariate analysis shows the level of knowledge (P: 0.037, CI: 0.001 to 0.089). There is a significant relationship between knowledge about HIV / AIDS with the attitude of stigma against people living with HIV. Recommendation from this research is to increase the systematic and comprehensive counseling or education about HIV / AIDS among the students of Kuningan School of Health Sciences to further increase student knowledge.